Uncovering the Value of a Historical Paper-Based Collaborative Artifact: The Nursing Unit's Kardex System - Mount-Campbell, Austin F.; Evans, Kevin D.; Woods, David D.; Chipps, Esther; Moffatt-Bruce, Susan D.; Patel, Kashvi; Patterson, Emily S. (Frontiers in Digital Health, 2020)
We identify useful functions and usability characteristics of a historical cognitive artifact used by nurses working in a hospital unit, the Kardex. By identifying aspects of a widely used artifact, we uncover opportunities to improve the usefulness of current systems for hospital nurses. We conducted semi-structured interviews with registered nurses about their prior experience with the Kardex. Questions included what elements of the Kardex are missing from their current electronic support. Memos were generated iteratively from interview transcript data and grouped into themes. Eighteen nurses from multiple clinical areas participated and had a median of 25-29 years of nursing experience. The themes were: 1) a status at a glance summary for each patient, 2) a prospective memory aid, 3) efficiency and ease of use, 4) updating information required to maintain value, 5) activity management, 6) verbal handover during shift-to-shift report, 7) narrative charting and personalized care, and 8) non-clinical care communication. Implications for digital support are to provide immediate, portable access to a standardized patient summary, support for nurses to manage their planned activities during a series of shifts, provide unstructured text fields for narrative charting, and to support adding informal notes for personalized care.